The Challenge of Sustaining Student Loan System: Colombia and Chile - Salmi, Jamil (International Higher Education, 2013)
Traditional, mortgage-type student loan schemes are vulnerable by design, as illustrated by the problems faced by the Chilean and Colombian agencies in recent years. Without an income-contingent provision, times of economic crisis are bound to create difficulties, as unemployment rises and incomes stagnate. This article documents the challenges encountered in these two Latin American nations and draws a few lessons that could help strengthen existing student loan systems.